Mediação: reflexões no campo da Ciência da Informação - Ana Amelia Lage Martins (2010)
This work, theoretically, was intended to produce a reflection on the use of the term mediation in the studies of science information in Brazil that are dedicated to understanding the multiple informational dynamics from various perspectives. Its starting point was a consideration of the current use of the concept of vast magnitude and significance in the area that is commonly associated to information, assigning, often, practices, processes and models of the most varied. This constant presence, and sometimes the term undefined in the area, bring questions and shedlight becomes significant for the ways in which its insertion occurs, the usage and ownership, since the mediation does not originate from the field, having been transported to this. A great effort was undertaken to systematize and discuss the usage of mediation in the field ofscience information produced in Brazil, trying to draw a "mapping" of the term and the major tasks assigned to it. It was aimed at guiding the seizure, the theoretical point of view, the main formulations that surround the word mediation in the area, through techno-scientific publications, which revealed the conceptual and theoretical treatment given the term. A corpus was made up of textual analysis with material from scientific meetings and articles in specialized journals in Science Information, composed of 164 sampling units based on the criteria of homogeneity, representativeness and relevance. It has come to a descriptive andanalytical way, funded by the technique of content analysis, which has led to the perception of a lack of conceptual treatment given to mediation as well as an absence of problems tackled and reflected on its meaning. It was seen that it is understood predominantly through the prism of the intermediate links that connect users and information and facilitating access to information. This vision converges to the notion of mediationrooted in common sense and reiterates an operational nature of the information in the field, making it difficult to epistemological rupture needed to do science. The analysis has allowed to point out the limitations and challenges inherent in the intricate task of understanding the different nuances that involve information and mediation in their everyday practices and processes. From such context it was possible to point a prospect to think about mediation in their relations with information gleaming, more closely, the discussions raised by theinseparable trinomial Information, Culture and Society. It was reached, and, through dialogue between the theoretical discussions and empirical data analyzed, the initial formulation of a construct called "mediation informational that seeks to give relief to the symbolic dimension,contradictory and conflicting, which characterizes the relationship between mediation and information.